Kaderisasi DAI NU Untuk Meningkatkan Kualitas Keislaman dan Kebangsaan di OKU Timur - Ahmad Sodikin; Sholeh Hasan; Ahmad Ulin Ni’am (Jurnal Indonesia Mengabdi, 2022)
The regeneration of DAI NU is carried out with the aim of producing DAI regeneration who have broad insight into Islam, are brave and firm in conveying the truth, have national insight and insight into Ahlusunnah wal Jama'ah, are able to spread Islamic traditions that are friendly, tolerant and have good morals and become good role models. for the community, able to convey Islamic da'wah in the realm of ukhuwah Islamiyah, ukhuwah bashariyah, ukhuwah wathoniyah. The implementation steps start from (1) deliberation of the service team with the LDNU management; (2) participant recruitment; (3) Education and training; (4) Field Da'wah Practice; (5) evaluation. The resulting output is the formation of Dauroh DAI NU in East OKU which has received a certificate of education and training for DAI NU. The certificate in question is also a form of legality for preaching recommended by the East NU OKU PC.